(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Legal certainty must be have by a law because law must guarantee that certain boundaries are bound to act, so that clear boundaries are considered with certainty. Law without the value of certainty will lose the identity and meaning, because it can notbe longer used as a guideline for everyones behavior. The research method used in this study is normative legal research supported by an empirical approach. The empirical approach used in this writing is the decisions of the Commercial Court at the District Court. The existence of personal guarantees in bankruptcy Debtor Limited Liability to realize legal certainty. Legal certainty regarding repayment of Debtors debt obligations by Garantor can be reached through a Suspension of Payment or a Bankruptcy Request filed against the Debtor and Garantees simultaneously in the same case. Problems will arise if the Suspension of Payment or Bankruptcy application is submitted only to the Debitor without including the Garantees. Moreover, if the Debtor is in a state of bankruptcy, the assets of the Debtor are sold by the Reciever whose results will be shared with the Creditors. The remaining credit of the creditor who also has the right to collect from Garantees will be difficult to repay so that it does not provide legal certainty.